2018
DOI: 10.1542/peds.2018-0814
|View full text |Cite
|
Sign up to set email alerts
|

Use of CT for Head Trauma: 2007–2015

Abstract: CT neuroimaging did not decrease from 2007 to 2015. Findings suggest an important need for quality improvement initiatives to decrease CT use among children with head injuries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
48
1
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(53 citation statements)
references
References 36 publications
1
48
1
3
Order By: Relevance
“…Among those with a CT scan, 0.9% had ciTBI, defined as any of the following caused by TBI: death, receipt of neurosurgery, intubation >24 hours, or hospital admission >2 days associated with TBI on CT. Although Burstein et al 1 found a similar CT rate (32%), the current study hospital admission rate was only 2%, revealing a sustained use of CT scans despite apparently, on average, less severely injured patients compared with patients in the earlier PECARN cohort.…”
contrasting
confidence: 52%
See 2 more Smart Citations
“…Among those with a CT scan, 0.9% had ciTBI, defined as any of the following caused by TBI: death, receipt of neurosurgery, intubation >24 hours, or hospital admission >2 days associated with TBI on CT. Although Burstein et al 1 found a similar CT rate (32%), the current study hospital admission rate was only 2%, revealing a sustained use of CT scans despite apparently, on average, less severely injured patients compared with patients in the earlier PECARN cohort.…”
contrasting
confidence: 52%
“…In this month's Pediatrics, Burstein et al 1 report disappointing statistics in their work entitled "Use of CT for Head Trauma: 2007-2015." Using the National Hospital Ambulatory Medical Care Survey, a representative data set for emergency department (ED) visits, 2 they found that 32% of pediatric patients presenting for head trauma had computed tomography (CT) imaging as part of their evaluation.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…These community EDs thus hugely impact the care of pediatric patients nationwide. Previously published reports demonstrate that CTs are more frequently obtained in low‐ and intermediate‐risk head‐injured children by physicians with emergency medicine training compared to pediatric training and in nonteaching, suburban, and nonfreestanding children's hospitals . It follows that implementation of pediatric best‐practice guidelines such as the PECARN head injury decision tool within community EDs may have a large, positive impact on pediatric emergency care.…”
mentioning
confidence: 99%
“…A third of children with head injuries presenting to emergency departments in the United States receive imaging 3. The associated radiation risk for an individual child is low, but it becomes important at a population level.…”
mentioning
confidence: 99%